Development of lipid nanocapsules for antiangiogenic treatment of glioblastoma and evaluation of their potential for nose-to-brain drug delivery - Pourbaghi Masouleh, Milad (2019)
Glioblastoma (GB), the most aggressive, and the most frequent primary tumor of the brain in adults, present a prominent vascular proliferation. Innovative therapeutic agents targeting both angiogenesis and tumor cells are urgently required, along with competent systems for their delivery to the brain tumor. One such agent is sorafenib (SFN), a tyrosine kinase inhibitor. However, poor aqueous solubility and undesirable side effects limit its clinical application. The first objective of this thesis was to encapsulate this drug inside lipid nanocapsules (LNCs) to overcome these drawbacks. We developed LNCs with a high SFN encapsulation efficiency (> 90%) that inhibited in vitro angiogenesis and the viability of the human U87MG GB cell line. Intratumoral delivery of SFN-LNCs in mice bearing intracerebral U87MG tumors induced early tumor vascular normalization which could be used to improve the efficacy of chemotherapy and radiotherapy in the treatment of GB. The second objective was to define whether intranasal delivery of LNCs could be an alternative non-invasive route. In this regard, we investigated through Förster resonance energy transfer, the fate of dye-loaded LNCs across Calu-3 cell monolayers, a model of the nasal mucosa. We showed that employment of LNCs dramatically increased the delivery of the dye across Calu-3 cell monolayer but they were rapidly degraded after their uptake. These data highlight that LNCs are suitable nanocarriers for the local delivery of SFN but must be redesigned for enhancing their nose-to-brain delivery.